Analiza operacij kriznega upravljanja EU - Malešič, Marjan (Teorija in praksa, 2015)
The European Union (EU) pays a lot of attention to the security dimension of its functioning. This can be seen in the development of its security capabilities, performance of several civilian and military crisis management operations, preventing of conflicts, fighting terrorism, imposing economic sanctions and providing disaster relief within and outside the EU. The authors focus on a statistical analysis of completed and ongoing military and civilian crisis management operations and establish that the latter are not comprehensive and ambitious enough to promote the EU as an important and influential political and security actor in the world. In addition, the authors analyse two specific EU operations taking place in Bosnia and Herzegovina (ALTHEA) and Kosovo (EULEX) and identify the causes of the enormous differences in the levels of their efficiency.
Keywords: Bosna in Hercegovina; Bosnia and Hercegovina; Bosnia and Herzegovina; civilne operacije; Crisis management; ESDP; EU military mission [V4.3]; European Union; EVOP; Evropska unija; Kosovo; Krizno upravljanje; Military defence; Military missions; operacija Althea; operacija Eulex; skupna varnostna in obrambna politika; statistične analize; varnostna politika; Vojaška misija EU [V4.3]; Vojaška obramba; Vojaške misije; vojaške operacije